2017
DOI: 10.17943/etku.288488
|View full text |Cite
|
Sign up to set email alerts
|

Ters Yüz Sinif Modeli̇ Çerçevesi̇nde Gerçekleşti̇ri̇lmi̇ş Çalişmalara Bi̇r Bakiş: İçeri̇k Anali̇zi̇

Abstract: Ters yüz sınıf modeli, sınıf içinde geçen zamanı verimli hale getirmeyi hedefleyen pedagojik bir modeldir. Bu modelde öğrenenler, bilgi edinme gibi temel düzeyde beceri gerektiren görevleri okul dışında gerçekleştirirler. Uygulama, problem çözme, yaratıcılık gibi üst düzey becerileri gerektiren görevleri ise sınıfta, öğretmen rehberliğinde gerçekleştirirler. Bu çalışma kapsamında, ters yüz sınıf modelinin odak alındığı, 2011-2015 yılları arasında çeşitli veri tabanları üzerinde taranan çalışmalar, içerik anali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
(5 reference statements)
0
10
0
1
Order By: Relevance
“…In this method, the gains gained are permanent because the students actively participate in the course and play an active role in the center of their learning process. This generally coincides with the modern age's student-centered understanding (Canbay, 2012;Demirel, 2012). Videos watched at home and pre-recorded by the teacher can be used repeatedly according to the students' learning speeds.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…In this method, the gains gained are permanent because the students actively participate in the course and play an active role in the center of their learning process. This generally coincides with the modern age's student-centered understanding (Canbay, 2012;Demirel, 2012). Videos watched at home and pre-recorded by the teacher can be used repeatedly according to the students' learning speeds.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…One of the main reasons for this is that Cakiroglu and Ozturk (2016) included theses mostly from foreign literature to their studies. Similarly, in the study conducted by Aydin and Demirer (2017), academic achievement was found to be the most examined variable.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 78%
“…Apart from these two disciplines, it has been observed that the model is frequently used in social studies and mathematics education. In the study conducted by Aydin and Demirer (2017), it was observed that the studies were mostly in the field of mathematics and then in the field of foreign language education. It can be said that in both studies, the disciplines which were studied the most are common in terms of two disciplines.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bireylerin ihtiyaçları çağın değişimiyle farklılaşmış, geleneksel eğitim yaklaşımları bu gereksinimleri karşılayamamıştır. Öğrenme hızları farklı olan bireylerin aynı eğitime tabi oldukları yaklaşımlar yerine bireyin gereksinimlerini dikkate alan farklılaştırılmış öğrenme ortamları ile bireylerin öğrendiklerini gerçek hayata aktarabilecekleri öğrenme deneyimlerine ihtiyaç duyulmaktadır (Demirer & Aydın, 2017).…”
Section: Introductionunclassified